Trends in colorectal cancer by subsite, age, and gender over a 15-year period in Adana, Turkey: 1993-2008 - Gülşah SEYDAOĞLU,; Birol ÖZER,; Nilgün ARPACI,; Cem Kaan PARSAK,; İsmail Cem ERAY, (Turkish Journal of Gastroenterology, 2019)
-